Stress Distribution and Optimum Spacing Determination of Double-Withdrawal-Channel Surrounding Rocks: A Case Study of Chinese Coal Mine - Yanjun He; Jianhua Li (Shock and Vibration)
In this study, the 31113 fully mechanised working face in the Lijiahao Coal Mine was selected as the project background. The failure characteristics and optimum spacing of a double-withdrawal-channel surrounding rock were extensively investigated through field measurements, theoretical analysis, and numerical simulations. The following results were obtained. The loading influence range of the working face was fixed. Under the influence of mining, the stress distribution variation in the double-withdrawal channels with spacing and the influence of stress distribution on the surrounding rock stability of the withdrawal channels were determined. The optimum distance between the double-withdrawal channels to achieve the stability of the surrounding rock was at least 25 m, and engineering measures are required to limit the mining height in the final mining stage. The rationality of the main and auxiliary withdrawal channel spacing of 25 m and measures to limit the mining height in the final stage were demonstrated. The findings of this study provide a valuable reference for constructing the layout of withdrawal channels in the adjacent working faces of the same mining area.